Analysing economic contribution of tourism: insights from selected Southeast Asian countries = Analiza wkładu gospodarczego turystyki: spostrzeżenia z wybranych krajów Azji Południowo-Wschodniej - Hieu, Vu Minh; Yen, Hua Thi Bach (Zielona Góra: Faculty of Economics and Management Press)
Tourism is a potential sector that can contribute positively to economic growth if properly managed. The southeast Asian countries have identified tourism as a key sector that can enable them to achieve sustainable economic growth. This study analysed the economic contribution of tourism in five southeast Asian countries (Indonesia, Malaysia, Singapore, Thailand and Vietnam).
Keywords: turystyka; produkt krajowy brutto; zatrudnienie; inwestycje; Azja Południowo-Wschodnia; tourism; gross domestic product; employment; investment; Southeast Asia